Encyclopedia of educational leadership and administration - English, Fenwick W. (Thousand Oaks, Calif. : Sage Publications, 2006)
1. School management and organization--United States--Encyclopedias. 2. Educational leaderships--United States--Encyclopedias. 3. Public schools--United States--Encyclopedias. 4. English, Fenwick W.
v. 1. A-K -- v. 2. L-Z.
Includes bibliographical references and index.
Faculty
Keywords: School management and organization -- United States -- Encyclopedias; Educational leadership -- United States -- Encyclopedias; Public schools -- United States -- Encyclopedias